2013
DOI: 10.1074/jbc.m112.434183
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylethanolamine Deficiency in Mammalian Mitochondria Impairs Oxidative Phosphorylation and Alters Mitochondrial Morphology

Abstract: Background:The contribution of phosphatidylethanolamine (PE) to mammalian mitochondrial function was unknown. Results: A decrease in mitochondrial PE impairs cell growth, respiratory capacity, and ATP production and profoundly alters mitochondrial morphology. Conclusion: Mitochondrial PE is required for normal morphology and function of mammalian mitochondria. Significance: Modest reduction of mitochondrial PE might contribute to mitochondrial dysfunction in some disease states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
271
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(296 citation statements)
references
References 98 publications
(91 reference statements)
23
271
1
1
Order By: Relevance
“…Whereas the sequential enzymes for the synthesis of PC are not located in mitochondria, PE can be produced by the action of PSD, which is localized in the inner mitochondrial membrane. Similar to our present findings, another study reported that depletion of mitochondrial PE also causes abnormalities in mitochondrial function (23). Tasseva et al (23) showed that a defect in PSD causing a 20 -30% reduction in mitochondrial PE levels also leads to decreases in cell growth rate, respiration and ATP production, and disruption of the structure of cristae in CHO cells.…”
Section: Contsupporting
confidence: 81%
See 1 more Smart Citation
“…Whereas the sequential enzymes for the synthesis of PC are not located in mitochondria, PE can be produced by the action of PSD, which is localized in the inner mitochondrial membrane. Similar to our present findings, another study reported that depletion of mitochondrial PE also causes abnormalities in mitochondrial function (23). Tasseva et al (23) showed that a defect in PSD causing a 20 -30% reduction in mitochondrial PE levels also leads to decreases in cell growth rate, respiration and ATP production, and disruption of the structure of cristae in CHO cells.…”
Section: Contsupporting
confidence: 81%
“…Similar to our present findings, another study reported that depletion of mitochondrial PE also causes abnormalities in mitochondrial function (23). Tasseva et al (23) showed that a defect in PSD causing a 20 -30% reduction in mitochondrial PE levels also leads to decreases in cell growth rate, respiration and ATP production, and disruption of the structure of cristae in CHO cells. Because PE is a typical cone-shaped lipid that modulates the negative membrane curvature and tends not to form a bilayer during the membrane fusion process (24,25), a reduction in mitochondrial PE levels might affect mitochondrial inner membrane fusion.…”
Section: Contsupporting
confidence: 81%
“…In mammalian cells, ablation of PSD is often associated with fragmented/deformed and dysfunctional mitochondria (42,49,50). A knockdown of TgPSD1mt, on the other hand, did not affect the typical lariat shape morphology of the organelle in T. gondii (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The non-bilayer forming phospholipids PE and CL are required for full activity of the respiratory chain, which generates the membrane potential across the inner membrane (52,55,(57)(58)(59). Thus, we wondered whether the respiratory chain complexes were present and functional in PC-deficient mitochondria.…”
Section: Depletion Of Pc Impairs Protein Transport Into the Innermentioning
confidence: 99%
“…First, binding of preproteins to the TOM complex is disturbed in PE-and CL-deficient mitochondria (49,50). Second, the activity of the respiratory chain complexes, in particular of the cytochrome c oxidase (complex IV), is decreased in mitochondria with reduced PE or CL content (57)(58)(59). Consequently, the membrane potential is decreased, which leads to reduced protein translocation via TIM23 or TIM22 translocases (52,55,57).…”
mentioning
confidence: 99%